(untitled) (Research, Society and Development, 2021)
The medicinal and therapeutic use of Cannabis spp. has a long history in humanity, but the current National Drug Policy in Brazil still imposes a bureaucratic process for planting, producing and consuming the substance for medicinal purposes. This article aims to analyze and compare how morning entertainment programs from Globo and Record networks approached the medicinal use of cannabis derivatives in Brazil between 2014 and 2018, in which the social movements in favor of the release of medical marijuana for families of patients who do not respond to conventional treatments are highlighted. There was a significant change in the approach, with regard to lexical selection, of the broadcasters during the import clearance process. The second modification observed is the choice of sources for the interviews. If at first there is a strong representation of families, building a familiar image of substance use, over time they are replaced by doctors and neuroscientists.